The Place of Naïve Realism in Russell’s Changing Accounts of Perception - Stubenberg, Leopold (Roczniki Filozoficzne, 2024)
In this paper I describe the place of naive realism in Russell’s changing accounts of perception. I argue ‎for the following conclusions: (1) The early period, 1898-1910: I am inclined to think that the naïve ‎realism that Russell embraced so enthusiastically early on may not have been intended as a naïve ‎realism about perception, but as a metaphysical or semantical thesis. (2) The Problems of Philosophy ‎‎(1912): Russell abandons naïve realism (if, in fact, he ever held it) and presents a sense-datum version ‎of representative realism. (3) “On Matter” (1912): here we see Russell’s best attempt to defend ‎something very close to the standard doctrine of naïve realism. The objects of perception—the ‎‎“everyday material objects such as caterpillars and Cadillacs”—have, of course, undergone severe ‎reconstruction. But the resulting picture does capture the spirit of the doctrine. (4) The period from ‎‎1914 to 1927: though Russell’s thinking about perception underwent some significant changes during ‎this period—the sense datum theory is replaced by neutral monism—I try to show that the ‎distinction between the matter of physics and the thing of common sense is a constant feature of ‎Russell’s changing views. And I suggest that our perceptual relation the thing of common ‎sense (as logically reconstructed by Russell) can usefully be viewed as a limited sort of naïve realism. ‎‎(5) The period after 1927: the thing of common sense no longer features in Russell’s account of our ‎perceptual access to the world. The things we perceive are percepts, located in our private spaces. The ‎only material objects of which these percepts are parts are our brains. All other material objects are ‎beyond our perceptual reach and are accessible only via inference. This is the end of anything ‎resembling the traditional view of naïve realism in Russell’s account of perception. ‎